Perkembangan Madrasah di Indonesia, dari Lembaga Tradisional Menuju Pendidikan - Siti Asmatul Fauziah; Widia Kusuma; Sulis Maryati (CV. ITTC INDONESIA, 2026)
This study aims to examine the development of madrasahs in Indonesia from traditional Islamic educational institutions into modern educational institutions using a library research approach. The findings indicate that madrasahs emerged as a response to the Muslim community's need for an educational system that integrates religious and general knowledge. Their development has progressed through various historical periods, including the Dutch colonial era, the Japanese occupation, the Old Order, the New Order, and the Reform Era. In each period, madrasahs experienced significant changes in educational policies, curriculum, teaching methods, and institutional management. Government policies, such as the Joint Decree of the Three Ministers (1975), Law Number 2 of 1989 on the National Education System, and Law Number 20 of 2003 on the National Education System, further strengthened the position of madrasahs as an integral part of Indonesia’s national education system. In addition to gaining equal recognition with public schools, madrasahs have successfully adapted to the advancement of science, technology, and societal needs while maintaining Islamic values as their core identity. Therefore, madrasahs have transformed into modern, adaptive Islamic educational institutions that play a significant role in improving the quality of national education.